2020
DOI: 10.2147/cmar.s257526
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and Safety of Apatinib Treatment for Patients with Advanced Intrahepatic Cholangiocarcinoma</p>

Abstract: Purpose Effective treatment options for intrahepatic cholangiocarcinoma (ICC) are limited. This study was intended to explore the efficacy and safety of apatinib in advanced ICC with lymph node metastasis or distant metastasis. Patients and Methods The efficacy and toxicity of apatinib were evaluated in patients with ICC between November 2017 and March 2020 at the Second Affiliated Hospital of Anhui Medical University. Survival analysis was estimated using Kaplan–Meier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…Additionally, fewer AEs occurred in another study assessing apatinib for advanced cholangiocarcinoma, but similar findings have also been obtained for curative effect (rate of DCR 62.5% and the median PFS 95 days observed in our cohort versus the DCR rate 70.0% and the median PFS 3.0 months in that study). The difference in result might be explained by the fact that the dosage (250 mg/day) in that study was lower than in our study (500 mg/day), which may have affected the treatment response ( 39 ). Thus far, there has been no more robust evidence for the effect of the dose of apatinib set at 500 mg per day for the treatment of cholangiocarcinoma.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Additionally, fewer AEs occurred in another study assessing apatinib for advanced cholangiocarcinoma, but similar findings have also been obtained for curative effect (rate of DCR 62.5% and the median PFS 95 days observed in our cohort versus the DCR rate 70.0% and the median PFS 3.0 months in that study). The difference in result might be explained by the fact that the dosage (250 mg/day) in that study was lower than in our study (500 mg/day), which may have affected the treatment response ( 39 ). Thus far, there has been no more robust evidence for the effect of the dose of apatinib set at 500 mg per day for the treatment of cholangiocarcinoma.…”
Section: Discussioncontrasting
confidence: 71%
“…A prospective open-label phase II study (NCT03251443) indicated that apatinib as non-first-line therapy has promising anti-tumor activity, with ORR 11.5%, DCR 50.0%, and median PFS 2.0 months, for the pretreated advanced biliary tract cancers ( 35 ). Likewise, in another study of second-line apatinib monotherapy, ORR was 10.0% ( 36 ).…”
Section: Discussionmentioning
confidence: 90%